Common statistical concepts in the supervised Machine Learning arena - Rashidi, Hooman H.; Albahra, Samer; Robertson, Scott; Tran, Nam K.; Hu, Bo (Frontiers in Oncology, 2023)
One of the core elements of machine learning (ML) is statistics and its embedded foundational rules and without its appropriate integration, machine learning as we know would not exist. Various aspects of ML platforms are based on statistical rules and most notably the end results of the ML model performance cannot be objectively assessed without the appropriate statistical measurements. The scope of statistics within the ML realm is rather broad and cannot be appropriately covered in a single review article. Therefore, here we will mainly focus on the common statistical concepts that pertain to supervised machine learning (i.e. classification and regression) along with their interdependencies and certain limitations.